The Canon of Judo: Classic Teachings on Principles and Techniques - Llyr C. Jones (Revista de Artes Marciales Asiáticas, 2012)
Kyuzo Mifune. Tokyo: Kodansha International, 2004. 256 páginas. 26x19 cm. I.S.B.N.: 4-7700-2979-9.